Utility of serum cytokine testing to differentiate complicated common variable immunodeficiency in resource limited settings - Aditi Jogdand, BS; Karen M. Gilbert, PhD; Joseph S. Hong, BS; Andrew J. Pak, BS; Katherine Liu, BA; Uhuru Kamau, MS; Neha V. Khairnar, MS, MBA; Henry C. Ssemaganda, MD, MS; Daniel DiGiacomo, MD, MPH; Sara Barmettler, MD, MPH; Mei-Sing Ong, PhD; Jocelyn R. Farmer, MD, PhD (Journal of Allergy and Clinical Immunology: Global)
Background: Common variable immunodeficiency (CVID) is the most common, symptomatic inborn error of immunity (IEI) worldwide. CVID diagnosis requires lymphocyte subset analysis by flow cytometry to delineate risk for autoimmune and inflammatory (AI) disease, known as complicated CVID. In resource-limited settings, reduced access to flow cytometry limits CVID diagnostics. Objectives: We investigated the utility of serum cytokine testing, as compared to standard-of-care flow cytometry, for the diagnosis of AI disease in IEI and CVID. Methods: We performed a retrospective review of patients with International Classification of Diseases, Tenth Revision–coded IEI and extracted cytokine levels, tested on a clinically available serum-based multiplex assay of 13 parameters (soluble IL-2 receptor [sIL-2R], IL-1β, IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, IL-12, IL-13, IL-17, TNF-α, IFN-γ). We assessed the association of cytokine levels with AI disease and immunophenotypes using Wilcoxon test or Spearman correlation, statistically adjusted for multiple testing. We compared predictive values of cytokine levels and lymphocyte subsets, measured by the area under the receiver-operating characteristic curve. Results: In IEI and CVID, higher sIL-2R and IL-10 levels correlated with more AI complications per patient and more severe T-cell immunophenotypes. Composite receiver-operating characteristic curves for sIL-2R and IL-10, as compared to lymphocyte subsets (naive CD4+ T cells and class-switched memory B cells), had comparable diagnostic performance for AI disease in patients with IEI and CVID. These findings were validated in an independent IEI patient cohort. Conclusions: sIL-2R and IL-10 testing had statistically comparable diagnostic performance for complicated CVID as compared to the current standard-of-care using flow cytometry.